2020
DOI: 10.1186/s13052-020-0803-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cardiac output and cardiac index values measured by critical care echocardiography with the values measured by pulse index continuous cardiac output (PiCCO) in the pediatric intensive care unit:a preliminary study

Abstract: Background: Planning optimal fluid and inotrope-vasopressor-inodilator therapy is essential in critically ill children. Pulse index Contour Cardiac Output (PiCCO) monitoring is an invasive, hemodynamic monitor that provides parameter measurements such as cardiac output (CO), cardiac index (CI). Use of ultrasonography and critical care echocardiography by the pediatric intensivists has increased in recent years. In the hands of an experienced pediatric intensivist, critical echocardiography can accurately measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…A previous study indicated a strong positive correlation (p < 0.001, r = 0.985) between the cardiac output values measured by critical care echocardiography and PiCCO in pediatric patients. 33 In the present study, however, one main purpose for the use of ultrasonography for treatment guidance in the ICU was to reduce the need for invasive procedures. Therefore, PiCCO was not considered a routine monitoring item.…”
Section: Discussionmentioning
confidence: 82%
“…A previous study indicated a strong positive correlation (p < 0.001, r = 0.985) between the cardiac output values measured by critical care echocardiography and PiCCO in pediatric patients. 33 In the present study, however, one main purpose for the use of ultrasonography for treatment guidance in the ICU was to reduce the need for invasive procedures. Therefore, PiCCO was not considered a routine monitoring item.…”
Section: Discussionmentioning
confidence: 82%
“…Further, another recent study showed that echocardiography measurements of CO and CI were comparable to PiCCO measurements, which was non-invasive compared with PiCCO. This result indicated the limitation of PiCCO, and thus echocardiography measurement could be used to guide fluid and vasoactive-inotropic management of critically ill pediatric patients [14]. From Table 3, it was found that the observation group patients effectively shortened the length of stay in the ICU and reduced the mortality rate.…”
Section: Discussionmentioning
confidence: 92%
“…The management of the optimal fluid and inotropic-vasopressor-inodilator therapy in severely ill pediatric patients should be planned by calculating cardiac output while conducting fluid therapy and inotrope treatment in children with shock, 19 Correspondence to email nagehan_aslan@hotmail.com doi: 10.1002/ajum.12233 especially in shock conditions which result in high mortality and morbidity in severely ill children. 20 The rate of CCE use in cardiac output assessments was 31% in Turkey PICUs. 6 The latest two septic shock guidelines stressed the significance of the cardiac index calculations in treatment plans.…”
Section: Assessment Of Cardiac Output and Cardiac Indexmentioning
confidence: 99%
“…25 We have demonstrated that cardiac index measurements by CCE compare favourably with PiCCO measurements and may be as important as invasive PiCCO-monitoring measurements in the planning of the vasopressor-inotrope and fluid treatment for the severely ill pediatric patients. 20…”
Section: Assessment Of Cardiac Output and Cardiac Indexmentioning
confidence: 99%